Obtenção de hidrocarbonetos pelos processos de pirólise térmica e termocatalítica do óleo de piaçava (Attalea funifera) - Almeida, Thiago Claudino Mendes de (2020)
Aviation biokerosene include compounds hydrocarbons with chains between C8 and C16, while green diesel is consisted for hydrocarbons in the carbon range from C14 to C21. These hidrocarbons can be reached from pyrolysis processes of vegetable oils. Pyrolysis is a route that consists in thermochemical decomposition of feedstock that occurs in the absence of oxygen. Two variations of this process, the thermal pyrolysis and thermo-catalytic one, were applied to vegetable oil seed of piassava specie Attalea funifera. Initially it was analyzed the properties of the oil and, after thermogravimetric analysis, it was made thermals pyrolysis and the characterization of the pyrolytic oils obtained. The thermal and thermo-catalytic pyrolysis of piassava oil and commercial soybean oil occurred at a temperature of 450 oC, to comparative purposes. A piassava oil composition has 79.53% fatty acids from saturated chain, in which dodecanoic acid as the major fatty acid. The phenolic compound’s profile indicated the presence of 20 phenolics compounds on piassava oil. The thermal decomposition process of this oil, in inert atmosphere, occurs in a single step, in which had a loss of mass approximately 97%, with a range of 180 and 450 oC. At a rate of 5% (m/m), the Pd/C catalyst contributed to increase the percentage concentration of hydrocarbons (35.94%) in piassava pyrolytic oil. It is noteworthy that, possibly, in the beta scissions functions and at the same conditions, a thermal pyrolysis in soybean oil, resulting in hydrocarbons chains so shorter (C8-C16) than ones present in the pyrolytic oil obtained from thermal pyrolysis of piassava oil. In addition, after the thermo-catalytic pyrolysis of soybean oil with 5% Pd / C, aromatic compounds are observed in the pyrolytic oil